2016
DOI: 10.1080/17470218.2015.1024696
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-to-oestradiol ratio is associated with female facial attractiveness

Abstract: The relationship between facial shape and attractiveness has been extensively studied, yet few studies have investigated the underlying biological factors of an attractive face. Many researchers have proposed a link between female attractiveness and sex hormones, but there is little empirical evidence in support of this assumption. In the present study we investigated the relationship between circulating sex hormones and attractiveness. We created prototypes by separately averaging photographs of 15 women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Among lipid parameters, facial attractiveness, but not perceived health, was negatively related with triglycerides, LDL, and total cholesterol (although the latter relationship was not significant when p was adjusted for multiple testing), but not HDL level. Additionally, we confirmed the negative relationship between facial appearance (attractiveness and health) and BMI and testosterone levels (although the relationship was not significant when p was adjusted for multiple testing) and positive with estradiol level, reported in previous research 3,46,56,57 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Among lipid parameters, facial attractiveness, but not perceived health, was negatively related with triglycerides, LDL, and total cholesterol (although the latter relationship was not significant when p was adjusted for multiple testing), but not HDL level. Additionally, we confirmed the negative relationship between facial appearance (attractiveness and health) and BMI and testosterone levels (although the relationship was not significant when p was adjusted for multiple testing) and positive with estradiol level, reported in previous research 3,46,56,57 .…”
Section: Discussionsupporting
confidence: 88%
“…We hypothesized that the relationship between facial appearance and lipid profile may be driven by its impact on current and future health and/or by its role as a substrate for sex hormones synthesis 30 , which have been shown to be related with facial appearance 3,17,46 . However, although we confirmed the relationship between sex steroids and facial appearance, the lipid profile was only related with facial attractiveness and unrelated with facial health, and presumably it was not the level of sex hormones that explained the relationship between facial attractiveness and lipid profile, but rather BMI, negatively related with both, perceived facial attractiveness and health, but also lipid profile markers (whereas sex steroids were not related with lipid profile).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Jokela (2009) found that the more attractive women had a higher reproductive success and more children. Interestingly, female facial attractiveness has also been linked to estimates of fertility (Roberts et al, 2004) and to higher levels of sex hormones (Probst, Bobst, & Lobmaier, 2016;Puts et al, 2013), in addition to BMI (Han, Hahn, Fisher, Debruine, & Jones, 2016).…”
Section: Whrs and Fertilitymentioning
confidence: 99%
“…Unknown is also the correlation between the attractiveness and current levels of sex hormones. According to available publications, the testosterone-to-estradiol ratio and low testosterone levels were positively associated with women's facial attractiveness (3). Others have found that the interaction of progesterone and estradiol adversely affect the women's attractiveness as judged by men (4).…”
Section: Introductionmentioning
confidence: 99%